2020
DOI: 10.3390/min10080724
|View full text |Cite
|
Sign up to set email alerts
|

pXRF Measurements on Soil Samples for the Exploration of an Antimony Deposit: Example from the Vendean Antimony District (France)

Abstract: Mineral exploration is increasingly challenging in inhabited areas. To evaluate the potential of soil analysis by pXRF (portable X-ray fluorescence) as a low-footprint exploration technique, we revisited a historic Sb district in an agricultural area and performed shallow-soil sampling (Ah and B horizons) along profiles across known veins to capture the endogenic geochemical anomaly signals. Despite an expected bias between pXRF measurements and laboratory analyses, the former effectively located the Sb veins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…When confronting the individual results from each technique for the characterization of soils, the pXRF results are slightly better [44]. However, the combination of both techniques greatly improves the results [8,45], even providing good results when the values are below the limits of detection from the pXRF equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When confronting the individual results from each technique for the characterization of soils, the pXRF results are slightly better [44]. However, the combination of both techniques greatly improves the results [8,45], even providing good results when the values are below the limits of detection from the pXRF equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The geochemical studies enhance mostly the quantification and chemical behaviour of elements in specific environments, facing mobilisation conditions due to changes in pH, redox reactions, and mineral breakdown during mine drainage; e.g., [4][5][6]. The portable X-ray fluorescence equipment proved its usefulness for studying the metal contents of contaminated soils in numerous cases reported in the literature; e.g., [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the XRF signal is independent of the chemical environment of the atom, complex sample preparation is usually not required for this technique. 9,10 Additionally, the availability of portable X-ray fluorescence spectrometers has made the technique a frequently employed tool for rapid on-site detection in a diverse array of fields, including archaeology, 11 geological exploration, 12 and environmental protection. 13 However, due to its relatively low sensitivity, XRF is less applied when detecting trace heavy metals such as arsenic and thallium in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many studies [7,11,[13][14][15][16][17] have reported the performance of pXRF instruments based on QA/QC validation procedures using certified reference materials (CRMs), blank samples, and/or traditional laboratory analyses on site-specific samples, studying different groups of elements in various matrices. Moreover, pXRF analyses of soil, lato sensu, samples are usually performed on common elements such as base metal(loid)s (e.g., As, Cu, Fe, Mn, Pb, Zn), whereas, curiously, highly toxic elements such as Hg and Sb have not been considered or have not been found in concentrations high enough and were detected in a small number of studies, e.g., [18,19]. Thus, the main purpose of this research was to evaluate the advantages and disadvantages of the use of pXRF on samples collected from two different decommissioned mining areas in Italy characterised by Pb-Zn and (Hg-rich) Cu-Sb ore deposits found to have very low to very high concentrations of As, Cu, Hg, Pb, Sb, and Zn.…”
Section: Introductionmentioning
confidence: 99%